HUBUNGAN ANTARA KONSEP DIRI DENGAN KECENDERUNGAN GAYA HIDUP HEDONISME PADA MAHASISWI PSIKOLOGI UST YOGYAKARTA - Ayentia Brilliandita; Flora Grace Putrianti (JURNAL SPIRITS, 2015)
ABSTRACT Â This study aims to determine the relationship between self-concept and lifestyle trends hedonism student of Psychology, University of SarjanawiyataTamansiswaYogyakart. The hypothesis of this study is that there are ties between the negative self-concept and lifestyle of hedonism on a college student.The subjects were female students of UST Psychology Yogyakarta, 18-22 years old, female, amounting to 87 people. Measuring instrument used was a self-concept scale and the scale of the lifestyle of hedonism. Analysis of data using Product Moment correlation with SPSS statistics program version 17.0 for Windows.Based on the analysis Product Moment correlation coefficient between the variables of self-concept and lifestyle trends hedonism is -0.382 with a significance level of P = 0.000 (p <0.05). This shows that the hypothesis that there is a negative relationship between self-concept and lifestyle of hedonism in coed acceptable. This means that the lower the self-concept, the higher the tendency of hedonistic lifestyle, otherwise the higher the self-concept, the lower the tendency of hedonism lifestyle.Keywords: Adolescent Self-Concept, Lifestyle Trends Hedonism.